2021
DOI: 10.1038/s41467-021-25080-x
|View full text |Cite
|
Sign up to set email alerts
|

A common limiter circuit for opioid choice and relapse identified in a rodent addiction model

Abstract: Activity in numerous brain regions drives heroin seeking, but no circuits that limit heroin seeking have been identified. Furthermore, the neural circuits controlling opioid choice are unknown. In this study, we examined the role of the infralimbic cortex (IL) to nucleus accumbens shell (NAshell) pathway during heroin choice and relapse. This model yielded subpopulations of heroin versus food preferring rats during choice, and choice was unrelated to subsequent relapse rates to heroin versus food cues, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 61 publications
5
27
0
Order By: Relevance
“…Thus, models that identify subpopulations of opioid-choosers are vital for screening novel potential pharmacotherapeutics for OUD. We recently developed a preclinical choice model that identifies a subpopulation of rats that choose heroin over food and yields increased reward seeking for heroin cues over food cues [ 6 ]. Thus, we are uniquely positioned to screen novel potential OUD therapies that target choice behavior to reduce opioid taking and seeking.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, models that identify subpopulations of opioid-choosers are vital for screening novel potential pharmacotherapeutics for OUD. We recently developed a preclinical choice model that identifies a subpopulation of rats that choose heroin over food and yields increased reward seeking for heroin cues over food cues [ 6 ]. Thus, we are uniquely positioned to screen novel potential OUD therapies that target choice behavior to reduce opioid taking and seeking.…”
Section: Introductionmentioning
confidence: 99%
“…In PFC, ELA enhanced heroin-induced Fos overall, without affecting activity in NAc-projecting cells. Although projections from PFC into NAc mediate reward-seeking behaviors, including for opioids [ 87 89 ], this finding suggests that the PFC→NAc pathway is not overtly altered by ELA. ELA may thus instead alter other PFC neurons such as those targeting other brain regions—a possibility that should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2,8 ] Only studies that have employed extended drug access to exacerbate the addiction phenotype or drug priming, or those that have altered the price (e.g., increasing the number of lever presses required for the preferred reward) or delay in reward delivery (e.g., delaying the preferred reward) have managed to achieve a shift toward choosing drugs over natural rewards. [ 9,10 ] In our original manuscript describing these results, [ 1 ] we showed that even after abbreviated heroin access procedures, our rats still choose heroin over food approximately 50% of the time on average. Therefore, there are no obvious protocol differences between our study and others that offer a satisfying explanation for the surprising differences in behavioral outcomes.…”
mentioning
confidence: 91%
“…A key feature of an ideal preclinical model of OUD is individual variation in a population, with some individuals bearing the OUD phenotype (i.e., the vulnerable), and some individuals being resilient. [1,2] Opioid drugs like oxycodone, heroin, and fentanyl, are highly addictive, which is reflected by the incidence of continued use after exposure, often progressing to the clinical diagnosis of OUD. This simple fact is reflected by the nature in which the opioid epidemic evolved out of the overprescription of oxycodone for noncancer pain, which greatly expanded the proportion of the population ever exposed to opioids.…”
mentioning
confidence: 99%